Optimization of CO2 Sorption onto Spent Shale with Diethylenetriamine (DETA) and Ethylenediamine (EDA) - Asmau Iyabo, Balogun; Eswaran, Madiahlagan; Firas Ayad, Abdulkareem; Haylay Tsegab, Gebretsadik; Cecilia Devi, Wilfred; Hassan, Soleimani; Prasanna Mohan, Viswanathan; Boon Siong, Wee; Jemilat Yetunde, Yusuf (MDPI, 2022)
A novel technique was employed to optimize the CO2 sorption performance of spent shale at elevated pressure–temperature (PT) conditions. Four samples of spent shale prepared from the pyrolysis of oil shale under an anoxic condition were further modified with diethylenetriamine (DETA) and ethylenediamine (EDA) through the impregnation technique to investigate the variations in their physicochemical characteristics and sorption performance. The textural and structural properties of the DETA- and EDA- modified samples revealed a decrease in the surface area from tens of m2/g to a unit of m2/g due to the amine group dispersing into the available pores, but the pore sizes drastically increased to macropores and led to the creation of micropores. The N–H and C–N bonds of amine noticed on the modified samples exhibit remarkable affinity for CO2 sequestration and are confirmed to be thermally stable at higher temperatures by thermogravimetric (TG) analysis. Furthermore, the maximum sorption capacity of the spent shale increased by about 100% with the DETA modification, and the equilibrium isotherm analyses confirmed the sorption performance to support heterogenous sorption in conjunction with both monolayer and multilayer coverage since they agreed with the Sips, Toth, Langmuir, and Freundlich models. The sorption kinetics confirm that the sorption process is not limited to diffusion, and both physisorption and chemisorption have also occurred. Furthermore, the heat of enthalpy reveals an endothermic reaction observed between the CO2 and amine-modified samples as a result of the chemical bond, which will require more energy to break down. This investigation reveals that optimization of spent shale with amine functional groups can enhance its sorption behavior and the amine-modified spent shale can be a promising sorbent for CO2 sequestration from impure steams of the natural gas.